The Information of Historical Cost Earnings Relative to Supplemental Reserve-Based Accounting Data in the Extractive Petroleum Industry - Doran, B. Michael; Collins, Daniel W.; Dhaliwal, Dan S. (The Accounting Review, 1988)
[The perceived limitations of historical cost net income for assessing the relative performance of oil and gas firms led the SEC and FASB to issue a series of pronouncements requiring disclosure of current value reserve-based information to supplement the information contained in the primary financial statements. This study examines whether historical cost earnings of oil and gas companies possess information in the sense of explaining cross-sectional differences in firm security returns. Additionally, we examine whether various Reserve Recognition Accounting-based measures possess incremental information relative to historical cost earnings measurements. The results indicate that for the sample period 1979-1981, historical cost earnings as well as reserve-based measures constructed from RRA data contain information relevant to valuing oil and gas firms. However, these results deteriorate for the sample period 1982-1984 where reserve-based measures are constructed from SFAS No. 69 data. The weaker relations in the latter period are consistent with the findings of Miller and Upton [1985b] and Magliolo [1986] and are attributed to the relative stability of oil prices during this time frame which results in a lower "signal-to-noise" ratio for the various reserve-based measurements.]